Are there any differences betzeen ranitidin or famotidin plus dual antibiotic combination in patients with Helicobacter pylori positive nonulcer dyspepsia (Annals of Medical Research, 2021)
None
Keywords: Hsub2/sub blockers, amoxicillin, clarithromycin, Helicobacter pylori eradication.